The days between : blessings, poems, and directions of the heart for the Jewish High Holiday season = Yamim she-ben le-ven : berakhot shiriim, ṿe-khavanot ha-lev la-ʻAśeret yeme teshuvah - Falk, Marcia (HBI series on Jewish women., 2014)
An elegantly designed volume of new English and Hebrew prayers and reflections for the High Holidays from a contemporary American poet.